Sequence analysis and pathogenicity of Avian Orthoavulavirus 1 strains isolated from poultry flocks during 2015–2019 - Abd El-Hamid, Hatem S.; Shafi, Manal E.; Albaqami, Najah M.; Ellakany, Hany F.; Abdelaziz, Naglaa M.; Abdelaziz, Mohamed N.; Abd El-Hack, Mohamed E.; Taha, Ayman E.; Alanazi, Khalid M.; Elbestawy, Ahmed R. (BMC veterinary research, 2020)
Background Newcastle disease (ND) causes severe economic losses in poultry industry worldwide. Egyptian poultry industry suffered from severe economic losses since the isolation of Velogenic Newcastle disease virus (vNDV) genotype VIId in 2011 and up till now despite the use of different vaccination programs. So, this study aimed to isolate and characterize the vNDV from a total of 120 poultry flocks from ten provinces in the Egyptian Delta region with a history of respiratory manifestation, high mortalities or a decrease in egg production between 2015 and 2019. Seventy-three samples’ allantoic fluid (73/120, 60.8%) were positive for hemagglutination with chicken RBCs. These samples were submitted to molecular examination using qRT-PCR specific primers for AOAV-1, highly pathogenic avian influenza (HPAI-H5), low pathogenic avian influenza (LPAI-H9) and infectious bronchitis virus (IBV). Results Fifty samples (50/120: 41.6%) were confirmed positive for AOAV-1, based on genetic analysis of matrix and fusion protein. The co-infection rate of other respiratory viral diseases examined was 1.6, 14.1, and 4.1%, for HPAI-H5, LPAI-H9, and IBV, respectively. Biologically, the intracerebral pathogenicity index of ten selected AOAV-1 isolates ranged from 1.70 to 1.98, which indicated the velogenic nature of these isolates. All the sixteen sequenced isolates were AOAV-1 genotype VII.1.1. The full F gene sequence of six examined AOAV-1 VII.1.1 isolates contained the seven neutralizing epitopes, and the glycosylation motif of six-potential sites for N linked glycosylation at residues 85, 191, 366, 447, 471, and 541. Conclusion It could be concluded that the high prevalence of AOAV-1 genotype VII.1.1 in the Egyptian chicken flocks despite the intensive vaccination with live and killed ND vaccines, as all the 16 isolates tested were belonged to this genotype. Homologous vaccination is badly needed to control and reduce the spread of AOAV-1 genotype VII.1.1infection in Egyptian poultry flocks.